Inhibition or Adaptation? Disentangling Age-Related Cognitive Interference in Spoken Language Through the Garner Paradigm. - Chen, Xuanda; Zhu, Wenkai; Zeng, Lei (Journal of Speech, Language & Hearing Research, 2026)
Purpose: This study investigated the interaction between age-related inhibitory deficits and lifelong language experience in spoken language processing. We explored whether age-related cognitive interference is solely due to a general inhibitory decline or if adaptations in cue weighting strategies based on lifelong sensory integration experience also play a role. Method: We used a cross-linguistic Garner paradigm, comparing younger and older native Mandarin speakers' performance in tone discrimination tasks using native Mandarin and nonnative Thai. Participants judged if two stimuli had the same tone while ignoring irrelevant segmental variations in control and orthogonal conditions for both languages. Error rates and response times (RTs) were analyzed using mixed-effects models. Results: Older adults showed slower RTs than younger adults in both tasks, whereas accuracy remained comparable. Garner interference, reflected in RTs, was no greater in Mandarin but significantly greater in Thai for older adults compared to younger adults. Error rate patterns showed smaller Garner interference and age differences in the Mandarin task than in the Thai task. Conclusions: The findings suggest that age-related cognitive changes in Garner interference are not solely attributable to general inhibitory deficits but reflect a complex interaction with experience-driven adaptations in cue integration. Lifelong language experience appears to mitigate interference in familiar contexts, highlighting the adaptive role of experience in cognitive aging. This study shifts the perspective from a uniform inhibitory decline view to a dynamic aging view that emphasizes experience reliance and adaptive control. Supplemental Material: https://doi.org/10.23641/asha.30885359